The Level of Satisfaction with the Quality of Trans Mebidang Bus Service - Yusuf Aulia Lubis; Sirojuzilam Sirojuzilam; R A matondang; Suwardi Lubis (LPPM Universitas PGRI Adi Buana, 2022)
One company that provides buses serving the Medan-Binjai-Deliserdang route is the Trans Mebidang Bus. The services provided include punctuality, cleanliness, wi-fi, and others. Based on the facilities and services provided by the bus manager, the community will provide an assessment of the level of satisfaction of the service. Customer satisfaction can be analyzed using statistical methods. The author determines customer satisfaction with 5 dimensions, namely Reliability, Responsiveness, Assurance, Empathy, and Tangible. This research was conducted by interviewing 50 respondents with 15 questionnaires. From the results of our research, the Reliability dimension answered Good as much as an average of 42 respondents (82 persen), the Responsiveness dimension was 46 persen of respondents (78.5 persen), the Assurance dimension was 34, 67 respondents (69.22 persen), Empathy dimension 26.67 respondents (53.33 persen), Tangible dimension 53 persen, respondents (63.33 persen). So in general, almost all facilities provided by the Trans Mebidang Bus are felt well by customers